1988
DOI: 10.1017/s002221510010667x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed brainstem auditory evoked responses in diabetic patients

Abstract: The incidence of subclinical central diabetic neuropathy is unclear due to difficulty in detecting latent alterations of central neural transmission process. The aim of this study was to evaluate a central neuroconductive mechanism in diabetics by brainstem auditory evoked responses (BAER). We found increased latencies of peaks I, III, V in diabetics as compared to control subjects. These BAER abnormalities were demonstrated in 62 per cent of insulin-controlled diabetics and in 33 per cent o patients treated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 8 publications
0
18
0
3
Order By: Relevance
“…It has been confirmed by experiments that all BAEP waves PL and IPL were significantly delayed in diabetes patients (Donald et al, 1981;Buller et al, 1988;Liu et al, 1993;Ryu and Chin, 1995). Additionally, He et al (2004) demonstrated that there were significant prolongations of BAEP waves I, II, IV, and V PL of rats with diabetes by the 28th day, and wave III PL and I-V IPL were delayed on the 42th day, which was positively correlated with their courses.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…It has been confirmed by experiments that all BAEP waves PL and IPL were significantly delayed in diabetes patients (Donald et al, 1981;Buller et al, 1988;Liu et al, 1993;Ryu and Chin, 1995). Additionally, He et al (2004) demonstrated that there were significant prolongations of BAEP waves I, II, IV, and V PL of rats with diabetes by the 28th day, and wave III PL and I-V IPL were delayed on the 42th day, which was positively correlated with their courses.…”
Section: Discussionmentioning
confidence: 81%
“…In 1981, Donald et al (1981) made use of brain stem auditory evoked potential (BAEP) to study diabetes. Afterward, research showed that waves V peak latency (PL) and waves I-V interpeak latency (IPL) were significantly delayed in diabetes (Buller et al, 1988;Liu et al, 1993;Ryu and Chin, 1995) suggesting that the central brainstem function was damaged. There is no effective treatment or drug for electrophysiological abnormalities, and the mechanism leading to the functional loss of brain neurons is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, not all authors agree that diabetes mellitus can lead to a sensorineural hearing impairment. [13][14][15] The effects of different variables such as duration of diabetes, blood sugar control, and presence of end-organ damage on hearing loss have yet not been clarified despite several studies on this topic. 9 Although there is mounting evidence for a relationship between diabetes and hearing impairment the awareness of auditory organ involvement in the course of diabetes is still not widespread among healthcare providers involved in diabetes care.…”
Section: Introductionmentioning
confidence: 99%
“…Along with biochemical and molecular-biological studies, electrophysiological investigations (using electroencephalography [12] and the method of evoked potentials [8,11] are being carried out; however, studies directly devoted to specilicities of neuronal activity are lacking.…”
mentioning
confidence: 99%